Implementing electronic health records on a medical service trip improves the patient care process - Maarsingh, Harm; Oyler, Kayla; Tuhaise, Gamukama; Sourial, Mariette; Nornoo, Adwoa O.; Moses, Wambazu; Rhodes, Laura A. (Frontiers in Health Services, 2022)
Background The efficiency of the patient care process of short-term medical service trips is often not assessed. The Gregory School of Pharmacy has organized annual medical camps in rural Uganda, however, the paper health records used for documentation and communication between stations have shown several limitations that hinder an optimal patient care process. Therefore, our objective was to implement an electronic health record system in these medical camps to improve the workflow and optimize the patient care process. Methods An electronic health record system that functioned over a battery-operated local area network was developed and implemented. Patient health information was entered and reviewed at the different stations using mobile devices. The impact of electronic health records (used in 2019) on the patient care process was assessed using the number of patients served per physician per hour and the number of prescriptions filled per hour and comparing these to paper records (used in 2017). Results Electronic health records were successfully implemented and communication across stations was fluid, thus improving transitions. Importantly, 45% more patients were served per physician per hour and 38% more prescriptions were dispensed per hour when using electronic (2019) compared to paper records (2017), despite having a smaller team in 2019. Conclusion Implementation of electronic health records in rural Uganda improved the patient care process and the efficiency of the medical camp.